Psalm 145: All Flesh Will Bless God's Holy Name. - Declaissé-Walford, Nancy L. (Catholic Biblical Quarterly, 2012)
A literary criticism of the biblical text Psalm 145 is presented. It aims to explain the widespread Jewish liturgical use of this Psalm. It analyzes the alphabetic acrostic structure, the lyrical acoustic qualities, and the rhetorical outline of the psalm. The author claims that these factors influence liturgical reciters of the psalm, by drawing them into a symbolic world in which YHWH is king.